Antibodies to myelin oligodendrocyte glycoprotein in idiopathic optic neuritis. Issue 4 (2nd April 2015) - Nakajima, Hideki; Motomura, Masakatsu; Tanaka, Keiko; Fujikawa, Azusa; Nakata, Ruka; Maeda, Yasuhiro; Shima, Tomoaki; Mukaino, Akihiro; Yoshimura, Shunsuke; Miyazaki, Teiichiro; Shiraishi, Hirokazu; Kawakami, Atsushi; et al.
Abstract : Objectives: To investigate the differences of clinical features, cerebrospinal fluid (CSF), MRI findings and response to steroid therapies between patients with optic neuritis (ON) who have myelin oligodendrocyte glycoprotein (MOG) antibodies and those who have seronegative ON. Setting: We recruited participants in the department of neurology and ophthalmology in our hospital in Japan. Methods: We retrospectively evaluated the clinical features and response to steroid therapies of patients with ON. Sera from patients were tested for antibodies to MOG and aquaporin-4 (AQP4) with a cell-based assay. Participants: Between April 2009 and March 2014, we enrolled serial 57 patients with ON (27 males, 30 females; age range 16–84 years) who ophthalmologists had diagnosed as having or suspected to have ON with acute visual impairment and declined critical flicker frequency, abnormal findings of brain MRI, optical coherence tomography and fluorescein fundus angiography at their onset or recurrence. We excluded those patients who fulfilled the diagnostic criteria of neuromyelitis optica (NMO)/NMO spectrum disorders (NMOSD), MS McDonald's criteria, and so on. Finally we defined 29 patients with idiopathic ON (14 males, 15 females, age range 16–84 years). Results: 27.6% (8/29) were positive for MOG antibodies and 3.4% (1/29) were positive for AQP4. Among the eight patients with MOG antibodies, five had optic pain (p=0.001) and three had prodromal infection (p=0.179). Three of the eight MOG-positive patients showed significantly high CSF levels of myelin basic protein (p=0.021) and none were positive for oligoclonal band in CSF. On MRIs, seven MOG-positive patients showed high signal intensity on optic nerve, three had a cerebral lesion and one had a spinal cord lesion. Seven of the eight MOG-positive patients had a good response to steroid therapy. Conclusions: Although not proving primary pathogenicity of anti-MOG antibodies, the present results indicate that the measurement of MOG antibodies is useful in diagnosing and treating ON.